Income inequality and growth in transition economies: Are nonlinear models needed? - Guang Hua Wan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper analyses the relationship between income inequality and growth in transition economies. The distinct and complex dynamics adherent to these economies lead to the proposition of new econometric models in the paper. However, empirical results do not support the proposed more flexible nonlinear functions. Further, the Kuznets hypothesis is clearly rejected by our data. On the contrary, a (first) half U pattern is found to be adequate for describing the inequality-growth relationship. Consequently, the rising inequality commonly observed in transition economies does not constitute part of the empirical regularity found by Robert Barro and others.
Keywords: O57; P20; O15; 330; Kuznets hypothesis; transition economies; functional form; inequality; Einkommensverteilung; Wirtschaftswachstum; Kuznets Kurve; Übergangswirtschaft